Analisis Media Monitoring Brand Facetology pada Bulan Maret - April 2024 Menggunakan Analysis Tools Brand24 - Hapsari Sholeha, Nadinda Alisya (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The beauty industry, especially the skincare sector, is experiencing rapid growth in Indonesia. Facetology, as one of Indonesia's local skincare brands, has succeeded in building a strong brand image through unique visual branding and quality products through social media. To maintain and improve the image that has been built, it is necessary to carry out analysis to determine sentiment, mentions and public reach of the company to develop its social media. In this research, researchers used descriptive qualitative research methods with a type of netnography using media monitoring analysis tools Brand 24. Sources of social media data collected by researchers from Brand24 were X (Twitter), TikTok, videos, news, forums, podcasts, blogs, and websites.